Manipulation of quantum dot emission with semiconductor metasurfaces exhibiting magnetic quadrupole resonances - Vaskin, Aleksandr; Liu, Sheng; Addamane, Sadhvikas; Vabishchevich, Polina P.; Yang, Yuanmu; Balarishnan, Ganesh; Sinclair, Michael B.; Pertsch, Thomas; Brener, Igal; Staude, Isabelle (Optics Express, 2021)
Optical metasurfaces were suggested as a route for engineering advanced light sources with tailored emission properties. In particular, they provide a control over the emission directionality, which is essential for single-photon sources and LED applications. Here, we experimentally study light emission from a metasurface composed of III-V semiconductor Mie-resonant nanocylinders with integrated quantum dots (QDs). Specifically, we focus on the manipulation of the directionality of spontaneous emission from the QDs due to excitation of different magnetic quadrupole resonances in the nanocylinders. To this end, we perform both back focal plane imaging and momentum-resolved spectroscopy measurements of the emission. This allows for a comprehensive analysis of the effect of the different resonant nanocylinder modes on the emission characteristics of the metasurface. Our results show that the emission directionality can be manipulated by an interplay of the excited quadrupolar nanocylinder modes with the metasurface lattice modes and provide important insights for the design of novel smart light sources and new display concepts.
CRIS-Team Scopus Importer:2023-04-20